Study of Genetic Similarity of Some Rootstocks and Grapevine Cultivars Using ISSR Technique (Journal of Hama University, 2020)
The research was carried out in the laboratories of the Atomic Energy Commission Molecular Biology and Biotechnology Department to identify the genetic diversity and genetic relatedness among four rootstocks and four grapevine cultivars (Vitis vinifera L.). Using the ISSR technique. By applying 24 primers for this purpose. Results indicated that 18 primers proved their effectiveness in showing polymorphism among the genotypes examined and the primers gave 430 bands, 376 of them were polymorphic, with polymorphic percentage of 87.40 %. The different primers revealed different levels of polymorphic percentage among the studied rootstocks and the cultivars. Primers (A42, A4) gave the highest polymorphic percentage (100%), while primer B5 gave the lowest polymorphic percentage (50%). The highest genetic similarity (0.67) was between cultivars Black eanuni and Salty, while the lowest value (0.34) was between rootstock Ru140 and cultivar Salty. Cluster analysis grouped rootstocks and cultivars in separate clusters. ISSR unique band was estimated (133 unique band; 104 positive and 29 negative), It was concluded that ISSR technique could be used efficiently to emphasize, identify, onsure and evaluate the genetic diversity of grapevines.